Kinetics of radical copolymerization of [1-(fluoromethyl)vinyl] benzene with chlorotrifluoroethylene - Kostov, G; Tredwell, M; Gouverneur, V; Ameduri, B (2007)
The synthesis of [1-(fluoromethy'l)vinyl]benzene (or α-(fluoromethyl) styrene, FMB) and its radical copolymerization with chlorotrifluorethylene (CTFE), initiated by tert-butyl peroxypivalate (TBPPi) are presented. The allyl monomer [H2C = C(CH2F)C6H5] was obtained by electrophilic fluorodesilylation of trimethyl(2-phenylprop-2-en-1- yl)silane in 93% yield. A series of seven copolymerization reactions were carried out starting from initial [CTFE0([FMB]0 + [CTFE]0) molar ratios ranging from 19.6 to 90.0 mol %. The molar compositions of the obtained poly(CTFEco-FMB) copolymers were assessed by means of 19F nuclear magnetic resonance spectroscopy. Statistic copolymers were produced with molar masses ranging between 13,800 and 25,600 g/mol. From the Kelen and Tudos method, the kinetics of the copolymerization led to the determination of the reactivity ratios, ri, of both comonomers (rCTFE = 0.4 ± 0.2 and rFMB = 3.7 ± 1.8 at 74 °C) showing that FMB is more reactive than CTFE as well as other halogenated or nonhalogenated monomers involved in the radical copolymerization with CTFE. © 2007 Wiley Periodicals, Inc.